2012
DOI: 10.1177/1753465812468043
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility evaluation of oral pressure therapy for the treatment of obstructive sleep apnea

Abstract: Abstract:Objective: This feasibility study examined the initial-use safety and potential utility of a novel noninvasive oral pressure therapy (OPT) system designed to reduce airway obstruction during sleep. Methods: This was a single-center, proof-of-concept, single-treatment-night study in which subjects with obstructive sleep apnea (OSA) underwent a baseline polysomnography (PSG) study followed by PSG during use of an OPT system. The OPT system is composed of a bedside console, a polymer mouthpiece, and a fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The results of this study confirm the feasibility of OPT for treatment of OSA as reported previously in a study of OPT in a different cohort of 71 subjects with OSA using individually customized mouthpieces 10. The magnitude of AHI reduction in the present study was similar to the reduction from 34.4 ± 28.9 (mean ± SD) events per hour to 20.7 ± 23.3 events per hour found in the prior study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study confirm the feasibility of OPT for treatment of OSA as reported previously in a study of OPT in a different cohort of 71 subjects with OSA using individually customized mouthpieces 10. The magnitude of AHI reduction in the present study was similar to the reduction from 34.4 ± 28.9 (mean ± SD) events per hour to 20.7 ± 23.3 events per hour found in the prior study.…”
Section: Discussionsupporting
confidence: 91%
“…The console creates vacuum in the oral cavity intended to pull the soft palate anteriorly to decrease airway obstruction during sleep. A previous study evaluated this approach using mouthpieces customized for each subject 10. A new version of the OPT mouthpiece has been developed and is now available in ten standard sizes to accommodate a range of oral dimensions in individuals without requiring a custom production process for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…OPT is generally well tolerated but initial side effects are commonly noted. 20 In the feasibility study, device-related side effects were reported by 32% of the subjects, but 92% of the side effects were mild. The most common side effect in the multicenter study 19 was oral tissue discomfort or irritation.…”
Section: Discussionmentioning
confidence: 98%
“…Oral pressure therapy: Whereas, use of CPAP opens up the airway in sleep induced collapse by means of positive pressure applied to the nose acting as a pneumatic splint, use of oral pressure therapy, by means of vacuum applied to the oral cavity, ensures that the tongue and soft palate do not fall back to decrease the upper airway lumen in sleep in patients with SDB, with or without anatomic defects 52 . The device has two components, a vacuum generator with a console which is placed outside and an intra-oral device, consisting of mouth pieces of various sizes.…”
Section: Novel Methods For the Treatment Of Osamentioning
confidence: 99%